A rare case of subungual melanoma - Rajesh Verma; Sunita Kakkar; Biju Vasudevan; Vandana Rana; Debdeep Mitra; Shekar Neema (Wolters Kluwer Medknow Publications, 2015)
A 51-year-old male presented with blackish discoloration of nails of 10 months duration. Examination revealed black dystrophic left thumb finger nail. Detailed examination showed a mass under the dystrophic nail. Hutchinson sign was positive. Histopathology revealed characteristic features of melanoma. A detailed evaluation revealed no features of local or distant metastasis. The entire lesion was then removed surgically along with disarticulation at the interphalangeal joint. Resection-free margin was confirmed. This case is being reported for the rare occurrence of subungual melanoma in the Indian population and also for presentation with a long history of lesion with no evidence of metastasis.